The Effect of Using Context-Based Learning Videos on Fluid Materials on Students Critical Thinking Ability - Yulaisa, Gusni; Desnita, Desnita (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Starting from the learning media used in schools not being able to prepare students to think critically, using context-based learning videos is one solution to improve students' critical thinking abilities. This research aims to see the effect of context-based learning videos on fluid material on the essential thinking abilities of class XI students at SMA Negeri 5 Solok Selatan. This study uses a quasi-experiment with a posttest-only control design. The research population was all class XI IPA students at SMAN 5 Solok Selatan registered in the 2022/2023 academic year. Purposive sampling was chosen as a sampling technique, so classes XI IPA 1 and XI IPA 2 were taken as research samples. The instrument used to obtain critical thinking ability data was a written test using 8-item essay questions. Normality, homogeneity, and t-tests were used in the data analysis. The measurement results show that experimental class students (80,38) have higher critical thinking skills than the control class (70,56). Statistical analysis with the t-test shows that that tcount > ttable (3,41 > 2.006) means the working hypothesis is accepted. So, it can be concluded that using context-based learning videos on fluid material affects students' critical thinking abilities.